Exploitation of Antarctic krill (Euphausia superba) on its fishery grounds in the waters Antarctic (AREA 48) during the autumn-winter period of 2004 - N. N. Zhuk (Ukrainian Antarctic Journal, 2013)
In article the analysis was presented on fishing activity of Ukrainian and American vessels RKTS «Constructor Koshkin» and RTMS «Top Ocean» on the fishing of Antarctic krill Euphausia superba on the Area 48 (by FAO area). Oceanology and navigating conditions of fishing, their influence on its dynamics are examined. The reasons of formation and disintegration of commercial aggregations of krill are considered. The characteristic is given for size and mass composition and biological state of krill; as well as features of spatial distribution of size groups on the fishing areas at the Southern Orkney, Southern Shetland Islands and at the Island of South Georgia during the autumn-winter period of 2004. Examples of fishing gear influence on fish juveniles and marine mammals capture are considered.